Serum lactate dehydrogenase level as a possible predictor of treatment preference in psoriasis. Issue 2 (August 2021) - Koguchi-Yoshioka, Hanako; Watanabe, Rei; Matsumura, Yutaka; Ishitsuka, Yosuke; Inoue, Sae; Furuta, Junichi; Nakamura, Yoshiyuki; Okiyama, Naoko; Matsuzaka, Takashi; Shimano, Hitoshi; Fujisawa, Yasuhiro; Fujimoto, Manabu
Highlights: The serum LDH level correlates with the clinical improvement and are downregulated by apremilast in psoriasis. The serum LDH level reflects the oxygen consumption rate of blood T cells in the psoriatic patients. Our results imply that the metabolic skew in immune cells could be a treatment target in psoriasis. Abstract: Background: The efficacy of small molecule inhibitors for intracellular signal mediators varies among the individuals, and their mechanism of action is broad. A phosphodiesterase 4 inhibitor apremilast shows a dramatic effect on a certain proportion of psoriatic patients by modulating the cellular metabolism and regulating the production of pro-inflammatory molecules. However, it is unclear to which disease subtype this drug benefits. While psoriasis is a Th17-mediated disease, how immune cells are affected by the modulation of cellular metabolism is not fully evaluated, either. Objective: This study aims to identify the indices which predict the efficacy of apremilast in psoriasis, and to investigate the impact of metabolic activity in immune cells on the psoriatic pathogenesis. Methods: The association of treatment efficacy with clinical and laboratory data of the 58 psoriatic patients was evaluated. The reflector of the associated index was also sought among the indices of cellular metabolic pathways by use of an extracellular flux analyzer. Results: There was a correlation between clinical improvement and the serum lactate dehydrogenase (LDH) level in the patients treated with apremilast but not in those with biologics. Serum LDH level did not correlate with the cutaneous disease severity but correlated with the oxygen consumption rate of blood T cells. Conclusion: Psoriatic patients with high serum LDH level can be benefitted by apremilast. The serum LDH level reflects the augmented respiratory activity of T cells in psoriasis. Our results would highlight the importance of regarding metabolic skew in immune cells as a treatment target in psoriasis.